Studies on the Thermal properties of untreated and chemically treated Palmyra Palm Leaf Base Fibres - Thiruchitrambalam, M; Shanmugam, D; Thiru Murugan, Rama.; Venkateswaran, N (International Journal of Engineering and Technology, 2026)
Palmyra( Borassus flabefllier )palm leaf base fibre, a natural fibre extracted from palmyra palm tree   was chosen and chemicals such as sodium hydroxide , benzoylchloride , and potassium permanganate for pre treatment procedures .  Effect of these treatments on the  thermal properties  were determined experimentally.
Keywords: Natural fibre; pre-treatments and thermal properties